2010
DOI: 10.1007/s13187-010-0075-0
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Reading Level: A Systematic Review of the Suitability of Cancer Education Print and Web-based Materials

Abstract: Background Consideration of categories related to reading comprehension—beyond reading level—is imperative to reach low literacy populations effectively. “Suitability” has been proposed as a term to encompass six categories of such factors: content, literacy demand graphics, layout/typography, learning stimulation, and cultural appropriateness. Our purpose was to describe instruments used to evaluate categories of suitability in cancer education materials in published reports and their findings. Methods We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 33 publications
7
54
0
6
Order By: Relevance
“…Our assessment of apps for inclusion of skill-building instructions and opportunities for continued engagement demonstrated that most apps met or partially met these criteria. Although Coulon and colleagues did not assess cultural sensitivity or readability, our findings regarding an absence of cultural sensitivity and low readability were consistent with other prior work [22,26].…”
Section: Comparison With Prior Worksupporting
confidence: 92%
“…Our assessment of apps for inclusion of skill-building instructions and opportunities for continued engagement demonstrated that most apps met or partially met these criteria. Although Coulon and colleagues did not assess cultural sensitivity or readability, our findings regarding an absence of cultural sensitivity and low readability were consistent with other prior work [22,26].…”
Section: Comparison With Prior Worksupporting
confidence: 92%
“…Materials were distributed at the discretion of the clinician as a supplement to direct face-to-face communication. Suitability, in terms of content, literacy demand graphics, layout/typography, learning stimulation, and cultural appropriateness 18 also varied across sites. We concluded that the current state of providing information and education about an ICU stay was a clinician-driven process, which was used inconsistently and was potentially either inadequate or overwhelming for patients and families.…”
Section: Context Of the Study And Current State Of Patient And Familymentioning
confidence: 99%
“…We recommend that communications be written at 5th-6th grade reading levels, because that can increase recipients' understanding without harming their perceptions of the communications' quality (Wong-Parodi et al 2013). The Flesch-Kincaid readability statistic can be used to assess the reading level needed to understand the presented text, and has been applied to evaluate the readability of surveys (Velez and Ashworth 2007), insurance policies (Dubay 2004), medical consent forms (Tait et al 2005), and patient education (Daraz et al 2011;Finnie et al 2010). This statistic has been reliably correlated with other established measures of readability, such as average word familiarity and passage length (Golinkoff 1975(Golinkoff -1976Kesselman et al 2007;Ley and Florio 1996;Spyridakis and Standal 1987;Surber 1992;Tuinman 1973).…”
Section: Prescriptive Researchmentioning
confidence: 99%